An introduction to quantitative economics - Haines, Brian (London ; Boston : G. Allen & Unwin, 1978)
The aim of this book is two fold. First to enable students to read and comprehend economic literature that employs econometric techniques as method of analyses. Second, to enable students to use econometric methods themselves in simple studies in class exercises and project work. The book is meant for second year students at the university of polytechnic level who hope to specialize in econometrics and statistics in their third year. The book is divided into two parts, each with four chapters. Chapter 1 discusses the meaning and scope of econometrics as well as the procedures of conducting an econometric study. Chapter 2 is a revision of basic statistics. Chapter 3 examines the use of ordinary least square methods in single linear regression equation. Chapter 4 discusses non-linear and multiple regression. Part Two begin with chapter 5 which examines the consequences of violations of the standard assumptions about the error term. Chapter 6 extends the discussion to distributed lag models and the use of dummy variables. Chapter 7 concerns some empirical studies in macroeconomics. Chapter 8 concludes the book with a brief discussion of structural equations and the identification problem.
Includes index.
Includes bibliographical references: p. 161-163.
rpm 01/08/2017; 18/04/2018
Loans
Keywords: Econometrics; Economics